2014
DOI: 10.1155/2014/814736
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Babinski Reflex Predicts Delayed Neuropsychiatric Sequelae in Chinese Patients with Carbon Monoxide Poisoning

Abstract: As the human population increased in China, the carbon monoxide is a serious environmental toxin in public health. However, predicting the delayed neuropsychiatric sequelae (DNS) of carbon monoxide poisoning (COP) has not been well studied. We investigated the independent predictors of DNS in patients with COP. This study was conducted at four hospitals in China. Data were retrospectively collected from 258 patients with COP between November 1990 and October 2011. DNS was the primary endpoint. A positive Babin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The incidence of DNS following CO poisoning varies widely from 3% to 46%, and the lag time ranges between 2 days and 6 weeks after exposure [ 8 11 ]. Because of the lack of standard diagnostic criteria, most reported DNS include a broad spectrum of neurological deficits, cognitive impairments, and psychological disorders ( Table 1 ) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of DNS following CO poisoning varies widely from 3% to 46%, and the lag time ranges between 2 days and 6 weeks after exposure [ 8 11 ]. Because of the lack of standard diagnostic criteria, most reported DNS include a broad spectrum of neurological deficits, cognitive impairments, and psychological disorders ( Table 1 ) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another possible factor is that patients with a higher risk for NS were prone to receive HBOT ( Table 1 ) in this study. The general indications for HBOT are also risk factors for NS [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ], and even though we have adjusted for age and comorbidities in the analyses, we were unable to adjust for all the other risk factors. As a results, patients who received HBOT had higher prevalence of having risk factors for NS in comparison with those who did not, and this would contribute to the higher incidence of NS associated with HBOT observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical characteristics (especially symptoms and signs) may reflect the severity of CO poisoning, and thus it is reasonable that they can be employed for the prediction of neurocognitive sequelae after CO poisoning. Studies have indicated that a longer duration of admission, CO exposure duration > 6 hours, systolic blood pressure < 90 mmHg, Glasgow Coma Scale score < 9, Mini-Mental State Examination score, a lack of pupil reflex and a positive Babinski reflex were associated with the development of DNS or neurological sequelae, 14 15 16 17 but voluntary exposure, headache and transient loss of consciousness failed to predict neurocognitive sequelae. 14 Of note, a loss of consciousness was found to be related to the development of neurological sequelae in other studies.…”
Section: P Redictive F Actorsmentioning
confidence: 99%